Implementasi Digital Marketing Sebagai Strategi Pemasaran Guna Meningkatkan Daya Saing UMKM Fashion di Sila Perspektif Ekonomi Islam - M. Dandi Delas Putra; Umar Sagaf; Jainuddin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The number of MSME players who market their products using traditional methods and MSME players in sila are still lacking in integrating Islamic economic principles in implementing digital marketing such as honesty, social justice, and gharar in online transactions which make it difficult for MSME players to reach a wider market. So this research aims to find out the Implementation of Digital Marketing as a Marketing Strategy to Increase the Competitiveness of Fashion MSMEs in Sila Islamic Economic Perspective. This research will be conducted in Sila, Bima Regency, West Nusa Tenggara. This research uses Qualitative Research with a Descriptive Approach. Data Collection Techniques are Observation, Interview and Documentation. Data Analysis Techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of this study, Digital marketing has proven to be an effective tool to increase the competitiveness of fashion MSMEs in Sila, both in terms of increasing sales, brand awareness, and market reach.